2010
DOI: 10.1007/s12035-010-8139-z
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Essential Fatty Acids Modulate Initiation and Progression of Neurodegenerative Disease

Abstract: The significance of the selective enrichment in omega-3 essential fatty acids in photoreceptors and synaptic membranes of the nervous system has remained, until recently, incompletely understood. While studying mechanisms of cell survival in neural degeneration, we discovered a docosanoid synthesized from unesterified docosahexaenoic acid (DHA) by a 15-lipoxygenase (15-LOX), which we called neuroprotectin D1 (NPD1; 10R,17S-dihydroxy-docosa-4Z,7Z,11E,13E,15E,19Z hexaenoic acid). This lipid mediator is a docosan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
58
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(61 citation statements)
references
References 61 publications
0
58
0
Order By: Relevance
“…Genomic LOX sequences occur in two domains (Bacteria, Eukarya) of terrestrial life (3). In mammals, LOXs have been implicated in the biosynthesis of lipid mediators (4,5), but they may also play a role in cell differentiation (6,7), apoptosis (8) and pathogenesis of inflammatory (9), hyperproliferative (10), and neurological (11) disorders. Targeted gene inactivation in mice provided useful information on the functionality of Alox12B (12R-lipoxygenase) (12) and Aloxe3 (epidermal lipoxygenase-3) (13), but Alox5 (5-lipoxygenase)- (14), Alox15- (15), and Alox12-deficient mice (16) do not show major defects unless challenged otherwise.…”
mentioning
confidence: 99%
“…Genomic LOX sequences occur in two domains (Bacteria, Eukarya) of terrestrial life (3). In mammals, LOXs have been implicated in the biosynthesis of lipid mediators (4,5), but they may also play a role in cell differentiation (6,7), apoptosis (8) and pathogenesis of inflammatory (9), hyperproliferative (10), and neurological (11) disorders. Targeted gene inactivation in mice provided useful information on the functionality of Alox12B (12R-lipoxygenase) (12) and Aloxe3 (epidermal lipoxygenase-3) (13), but Alox5 (5-lipoxygenase)- (14), Alox15- (15), and Alox12-deficient mice (16) do not show major defects unless challenged otherwise.…”
mentioning
confidence: 99%
“…DHA is not merely a structural membrane component but also a modulator of crucial neurochemical processes, gene expression, synaptic plasticity, memory formation and intracellular calcium concentration (Calder, 2009;Crawford, 2006;McNamara & Carlson, 2006;Sergeeva et al, 2005). In addition, similarly to what was observed in a number of inflammatory based systemic disorders, DHA and its peroxidated (cyclopentenone neuroprostanes) or enzymatically generated (neuroprotectins and resolvins) derivatives display potent antiinflammatory functions in psychiatric disorders as well as in acute and chronic neurodegenerative conditions (Bazan, 2006;Belayev et al, 2011;Calder, 2009;Ebert et al, 2009;Groeger et al, 2010;Musiek et al, 2008;Palacios-Pelaez et al, 2010).…”
Section: Introductionmentioning
confidence: 83%
“…7) Moreover, clinical studies found therapeutic effects of n-3 PUFAs against the risk of cardiovascular events, attention deficit hyperactivity disorder, 8) Alzheimer's disease, 9) depression, 10,11) and various other degenerative neurological disorders. 12) Thus, it has become apparent that n-3 PUFAs are involved in a variety of physiological functions.…”
Section: Introductionmentioning
confidence: 99%